Shining NIR light on ivory: A practical enforcement tool for elephant ivory identification. Issue 9 (9th August 2021) - Chaitae, Apinya; Rittiron, Ronnarit; Gordon, Iain J.; Marsh, Helene; Addison, Jane; Pochanagone, Suttahatai; Suttanon, Nattakan
Abstract: The elephant ivory trade remains controversial because of concerns about the extinction risk of elephants and the different needs of CITES member states. Thailand's situation is particularly contentious because of the different legal status among types of elephant ivory. Thai law allows the local sale of ivory from domesticated Asian elephants, which creates challenges for Thai enforcement officers in identification of ivory provenance. We investigated the capacity of non‐destructive Near Infrared (NIR) spectroscopy (600–1700 nm), combined with Partial Least Squares Discriminant Analysis (PLS‐DA), to discriminate between ivory from African, wild Asian and domesticated Asian elephants. Ivory spectra of 64 elephants were divided randomly into calibration and validation datasets. We were able to determine elephant ivory provenance at both the interspecies (African and Asian elephant ivory), and within species (wild and domesticated Asian elephant ivory) classifications with 100% accuracy. These results showed the potential use of handheld NIR spectrometers for rapid assessments of ivory provenance, as well as a forensic tool for wider enforcement. Abstract : Near Infrared (NIR) spectroscopy, combined with Partial Least Squares Discriminant Analysis (PLS‐DA), can determine elephant ivory provenance at both the interspecies and within species levels with 100% accuracy. Advantages in non‐destructive, timely, and cost‐efficient identification enable practical use of NIR spectrometers for enforcement officers.